Genetic testing in individuals with cerebral palsy. (10th June 2021) - May, Halie J; Fasheun, Jennifer A; Bain, Jennifer M; Baugh, Evan H; Bier, Louise E; Revah‐Politi, Anya; Roye, David P; Goldstein, David B; Carmel, Jason B
Abstract : AIM To determine which patients with cerebral palsy (CP) should undergo genetic testing, we compared the rate of likely causative genetic variants from whole‐exome sequencing in individuals with and without environmental risk factors. METHOD Patients were part of a convenience and physician‐referred cohort recruited from a single medical center, and research whole‐exome sequencing was completed. Participants were evaluated for the following risk factors: extreme preterm birth, brain bleed or stroke, birth asphyxia, brain malformations, and intrauterine infection. RESULTS A total of 151 unrelated individuals with CP (81 females, 70 males; mean age 25y 7mo [SD 17y 5mo], range 3wks–72y) participated. Causative genetic variants were identified in 14 participants (9.3%). There was no significant difference in diagnostic rate between individuals with risk factors (10 out of 123; 8.1%) and those without (4 out of 28; 14.3%) (Fisher's exact p =0.3). INTERPRETATION While the rate of genetic diagnoses among individuals without risk factors was higher than those with risk factors, the difference was not statistically significant at this sample size. The identification of genetic diagnoses in over 8% of cases with risk factors suggests that these might confer susceptibility to environmental factors, and that further research should include individuals with risk factors. What this paper adds There is no significant difference in diagnostic rate between individuals with and without risk factors. Genetic variants may confer susceptibility to environmental risk factors. Six causative variants were identified in genes not previously associated with cerebral palsy. Global developmental delay/intellectual disability is positively associated with a genetic etiology. Extreme preterm birth, stroke/brain hemorrhage, and older age are negatively associated with a genetic etiology. What this paper adds: There is no significant difference in diagnostic rate between individuals with and without risk factors. Genetic variants may confer susceptibility to environmental risk factors. Six causative variants were identified in genes not previously associated with cerebral palsy. Global developmental delay/intellectual disability is positively associated with a genetic etiology. Extreme preterm birth, stroke/brain hemorrhage, and older age are negatively associated with a genetic etiology. This original article is commented by MacLennan on page 1369 of this issue.